2013
DOI: 10.1186/1471-2407-13-122
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent endpoints as predictors of overall survival in multiple myeloma

Abstract: BackgroundSupporting health care sector decisions using time-dependent endpoints (TDEs) such as time to progression (TTP), progression-free survival (PFS), and event-free survival (EFS) remains controversial. This study estimated the quantitative relationship between median TDE and median overall survival (OS) in multiple myeloma (MM) patients.MethodsStudies (excluding allogeneic transplantation) published from 1970 to 2011 were systematically searched (PubMed). The nonparametric Spearman’s rank correlation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 86 publications
1
28
2
Order By: Relevance
“…Our findings suggest that the benefit of an extended PFS that was observed in the published clinical trials may lead to or be an indicator of an OS benefit, and provide evidence that PFS should be considered as a valid surrogate endpoint for OS in MM. A meta-analysis conducted by Félix et al [41] found that various time-based endpoints such as median PFS, TTP, or event-free survival predicted median OS, but they did not directly examine the relationship between PFS and OS based on treatment effects. If we consider validation of a surrogate endpoint as a 2-step process of (1) establishing that a surrogate endpoint predicts a final endpoint and (2) establishing that a relationship exists between the treatment effects on the surrogate and final endpoint [7], then this study can be considered as a second step in the process of validating PFS as a surrogate of OS in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that the benefit of an extended PFS that was observed in the published clinical trials may lead to or be an indicator of an OS benefit, and provide evidence that PFS should be considered as a valid surrogate endpoint for OS in MM. A meta-analysis conducted by Félix et al [41] found that various time-based endpoints such as median PFS, TTP, or event-free survival predicted median OS, but they did not directly examine the relationship between PFS and OS based on treatment effects. If we consider validation of a surrogate endpoint as a 2-step process of (1) establishing that a surrogate endpoint predicts a final endpoint and (2) establishing that a relationship exists between the treatment effects on the surrogate and final endpoint [7], then this study can be considered as a second step in the process of validating PFS as a surrogate of OS in MM.…”
Section: Discussionmentioning
confidence: 99%
“…(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)26,32,33,35,36,38,(40)(41)(42)47,49,50) The literature suggests that the relationship between PFS and OS can be different within the same cancer trial depending on the treatment applied or the therapy selected.…”
Section: Challenges For Analysing Pfs As a Surrogate Of Osmentioning
confidence: 99%
“…2) Treatment line (14,21,22,25,26,28,33,34,36,40,41,49,52) In some cases the analysis cannot validate the surrogacy for first line therapy, as distinct 3) Year of the trial (11,13,15,16,18,19,22,28,(31)(32)(33)(34)40) The importance of the year in which the clinical trial was conducted or published was explained by the number of drugs available having increased (11 and because the criteria applied to measure progression have changed (e.g. RECIST published in 2000 was modified in 2010 to mRECIST (54)).…”
Section: ) Type Of Treatment And/or Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, many bivariate failure time distributions are not well understood or widely used, and the dependence relationship are not intuitively expressed in general bivariate distributions. Alternatively, we will propose to use a survival regression model with TTP as a time‐dependent covariate to explicitly express the association of progression with the risk of death because the risk for death will usually increase upon cancer progression. We assume TTP distributed as T p ∼ f p ( t p | θ p ) and OS distributed as T d ∼ f d ( t d | θ d ) before disease progression and as Tdfd(tdtp|θd) after disease progression at t p , where fdcould be the same as or different from f d .…”
Section: Data Structure and Statistical Modelmentioning
confidence: 99%